Smart Crowdsensing Berbasis Smart Service untuk Pemulihan Sektor Kesehatan dan Ekonomi di Masa Pandemi - Amanda Putri Septiani (Jurnal Sistem Cerdas, 2021)
The use of intelligent systems and technology is very much needed during this Covid-19 pandemic. The reason is that there are many sectors that must be rescued immediately, such as health and the economy. On the one hand, the community must be saved from the ongoing epidemic, but on the other hand, economic activity must continue to be pursued even though it is not in ideal conditions. One solution to these problems is the design of Smart Crowdsensing based on smart services that can be used to support physical distancing but still stimulate economic activity to keep moving. In general, smart crowdsensing functions to (i) detect crowds using location data from the user's mobile device GPS, (ii) self-quarantine surveillance and contact tracing using position history in real time, and (iii) collect and process information from citizen interactions. on social media to find out citizen reports related to the pandemic. Smart crowdsensing is designed using a smart service engineering method that allows it to communicate with other services using a REST API.